Analisis Akuntabilitas Pelayanan Publik Dalam Kepatuhan Wajib Pajak (Studi Pada Kantor Pelayanan Penyuluhan Dan Konsultasi Perpajakan KP2KP Taliwang) - Nadira Fitria ningsi, Leni (Jurnal Administrasi Karya Dharma, 2024)
Taxes are one of the most dominant sources of state income for the survival of a nation. One indicator of a nation's independence is shown by the role of taxes in contributing to finances as reflected in the APBN or APBD. To increase understanding and responsibility of the state for taxpayers, tax laws and regulations are always reviewed and adapted to the socio-economic growth of the Indonesian State. The purpose of this research is to analyze the accountability of public services at the Taliwang tax counseling and consultation services office (KP2KP) in taxpayer compliance. The research method used in this research is descriptive qualitative, how a researcher conducts research regarding descriptive studies and tends to carry out analysis. The results of this research show that the analysis of public service accountability in taxpayer compliance with KP2KP Taliwang shows that it has used elements of agency accountability, so that it has formulated various programs and activities that can increase the accountability of its services, and has reached the level of public satisfaction in terms of its services and matters. which can support the achievement of improving the quality of public services, including the strong commitment of KP2KP Taliwang employees who have a significant influence so that the implementation process can run well and can support the achievement of accountability in taxpayer compliance at KP2KP Taliwang.